Estudo comparativo dos mecanismos de resistência aos β-lactâmicos em amostras clínicas de Pseudomonas aeruginosa isoladas de infecção de corrente sanguínea no Brasil e nos Estados Unidos da América - Fehlberg, Lorena Cristina Corrêa [UNIFESP] (2010)
The aim of this study was evaluate the mechanisms of β-lactams resistance in P. aeruginosa clinical isolates from two hospitals, located in Brazil and United States of America (USA). We have selected 145 P. aeruginosa isolated in blood cultures. Of those, 84 and 61 isolates were recovered from patients hospitalized in Hospital São Paulo – HSP (Brazil), and in Medical College of Virginia – MCV (USA), respectively. All strains were submitted to antimicrobial susceptibility testing by agar dilution. Investigation of carbapenemase activity of crude extracts was performed by UV spectrophotometric assays. Detection of ESBL- and MBL-encoding genes was conducted by PCR, followed by amplicon sequencing. The hyperexpression of efflux systems (ABM, CDJ, EFN and XY), AmpC chromosomal β-lactamase, as well as reduced OprD expression was evaluated by quantitative real time PCR (qRT-PCR), compared to that of PA01 reference strain. Isolates from HSP showed decreased susceptibility rates for most antimicrobials tested compared to those of MCV isolates, except for ciprofloxacin. Carbapenemhydrolysis was detected in seven P. aeruginosa from HSP, in which we have identified the MBL- encoding genes blaIMP-1 (n=1), blaIMP-16 (n=1) and blaSPM-1 (n=5). In addition, the production of GES-5 was observed in a single isolate from this hospital. In contrast, neither MBL- nor ESBL-encoding genes were observed in isolates from MCV. Efflux hyperexpression was more frequently observed in P. aeruginosa clinical isolates from HSP (71.4%) than from MCV (52.4%). The efflux systems XY (41.6%) and ABM (24.6%) were more frequently hyperexpressed in isolates from HSP and MCV, respectively. The simultaneous expression of different resistance determinants in one isolate was also evaluated. This association was more frequent among HSP isolates. Reduced OprD expression was similar among isolates from HSP and MCV, 91.6% and 91.8%, respectively. The hyperexpression of AmpC was 30.9% among HSP isolates and 5.0% among MCV isolates. The efflux hyperexpression and/or porin loss might increase β-lactam MICs, although not as effectively as do β-lactamases associated with other resistant determinants. This finding suggests that such mechanisms may favor P. aeruginosa survival under selective pressure, increasing its possibility to acquire other β-lactam resistance determinants in the hospital environment, contributing to the emergence of strains highly resistant to this class of antimicrobials.